Implementasi Perlindungan Hukum terhadap Pekerja Anak yang Mengalami Kekerasan menurut Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan (Studi Kasus Putusan Mahkamah Agung Nomor 294/PN.Tlg/2015) - Tantra Hadimulya; Syarif Fadhilla; Muhammad Fahruddin (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2020)
Manpower is an important part of driving the wheels of national development. The number and composition of the workforce which always changes along with the dynamics of growth and population density results in an imbalance between the number of labor force and available job vacancies. This situation is presumed to not only give rise to higher unemployment, but also lead to increasingly severe poverty. Due to the lack of economic pressure, children are required to help their parents in order to increase family income in order to fulfill their daily needs. In this paper, the author focuses on the formulation of the problem, namely: 1. How is the implementation of legal protection for child workers who experience violence according to Law Number 13 of 2003 concerning Manpower? 2. What are the hindering factors regarding the implementation of legal protection for child workers who experience violence according to Law Number 13 Year 2003 concerning Manpower ?. This study aims to find out what factors hinder the implementation of legal protection for child workers who experience violence according to Law Number 13 of 2003 concerning Manpower, to determine how the implementation of legal protection for child workers who experience violence according to Law Number 13 of 2003 About Employment. Where the descriptive research method aims to solve problems through collecting, compiling, and analyzing data to get answers to the main problem. From the main problem formulation raised in this paper, the authors conclude, that the implementation of legal protection for child workers who experience violence according to Law Number 13 of 2003 concerning Manpower is less effective.